Iraqi Kurdistan’s Statehood Aspirations
XI, 162 p. 6 illus., 3 illus. in color.
Keywords: This edited volume addresses the issues of Iraqi Kurdistan’s political economy with historically grounded, theoretically informed, and conceptually relevant scholarship that prioritizes comparative politics over international relations. The book seeks to explore the dynamics of Iraqi Kurdistan at the stage of referendum for independence from a political economy perspective within its own debates, conflicts, and interests. Overall, the authors contribute to these debates by exploring key questions in novel ways, focusing on comparative methodology that serve to expand the scope of scientific inquiry and place it into more solid understanding. .